split_scaffold_burbot_ref_long_94 - Underwood, Zachary E.; Mandeville, Elizabeth G.; Walters, Annika W. (Dryad Digital Repository, 2015)
Because there are no existing genomic resources for burbot, we constructed an artificial reference genome using smng (Seq- Man NGen, DNAstar), using 25 million reads. This artificial reference genome contains 53,789 contigs. We used this assembly as a template to for a reference-based assembly with bwa.